BACH1 recruits NANOG and histone H3 lysine 4 methyltransferase MLL/SET1 complexes to regulate enhancer–promoter activity and maintains pluripotency. Issue 4 (27th January 2021) - Niu, Cong; Wang, Siqing; Guo, Jieyu; Wei, Xiangxiang; Jia, Mengping; Chen, Zhaoxiong; Gong, Wenxuan; Qin, Yue; Wang, Xinhong; Zhi, Xiuling; Lu, Meng; Chen, Sifeng; et al.
Abstract: Maintenance of stem-cell identity requires proper regulation of enhancer activity. Both transcription factors OCT4/SOX2/NANOG and histone methyltransferase complexes MLL/SET1 were shown to regulate enhancer activity, but how they are regulated in embryonic stem cells (ESCs) remains further studies. Here, we report a transcription factor BACH1, which directly interacts with OCT4/SOX2/NANOG (OSN) and MLL/SET1 methyltransferase complexes and maintains pluripotency in mouse ESCs (mESCs). BTB domain and bZIP domain of BACH1 are required for these interactions and pluripotency maintenance. Loss of BACH1 reduced the interaction between NANOG and MLL1/SET1 complexes, and decreased their occupancy on chromatin, and further decreased H3 lysine 4 trimethylation (H3K4me3) level on gene promoters and (super-) enhancers, leading to decreased enhancer activity and transcription activity, especially on stemness-related genes. Moreover, BACH1 recruited NANOG through chromatin looping and regulated remote NANOG binding, fine-tuning enhancer–promoter activity and gene expression. Collectively, these observations suggest that BACH1 maintains pluripotency in ESCs by recruiting NANOG and MLL/SET1 complexes to chromatin and maintaining the trimethylated state of H3K4 and enhancer–promoter activity, especially on stemness-related genes.